STUDENTS' PERCEPTION ON THE USE OF WHATSAPP APPLICATION FOR ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Samsiya; Marzul Hidayat; Mukhlash Abrar (JAMBI-ENGLISH LANGUAGE TEACHING, 2022)
The impact of the spread of the covid-19 virus on the world of education requires educators and students to be adapted quickly to existing changes. Before the pandemic, the learning activity was original to be held face-to-face directly in the classroom, however, an integrated learning system through the virtual internet network (online learning) must be implemented during the pandemic. The implementation of English learning for students was still done online using WhatsApp. Based on this, the purpose of this study was to investigate students’ perceptions on the use of the WhatsApp application for online learning during the covid-19 pandemic. This study employed quantitative research with a survey method. This study used questionnaire data to collect the data. The results of questionnaire data analysis indicated that 122 of 168 respondents gave a good perception of the use of the WhatsApp application. In addition, the teacher used the features provided in the WhatsApp application, such as messages, voice messages, documents, videos, and images to improve students’ ability and evaluate the extent of students’ ability with the material that had been studied. The conclusion of the study is the existence of the benefits of WhatsApp media that teachers can use for learning English. Because WhatsApp has many advantages that support learning, this application can be used to send text messages, download and upload images, documents, or videos, and send voice messages.